(untitled) (Research, Society and Development, 2021)
The aim of this study is to stimulate discussion about the potential of social media as an important learning tool for healthcare professionals through a critical review of the literature. We conducted a critical brief review of the literature published from 2010 to 2021 in PubMed, using the search terms "social media", "healthcare professional", "online learning", "online education", and "medical education", and some variations according to MeSH. Besides the Pubmed database, searches were conducted through the website https://mededu.jmir.org/. Many healthcare professionals use social media to find and share health information, communicate with colleagues and trainees, advertise their clinical practices, engage in health advocacy, impact health policy decisions, exchange developments in their fields, and publicize their research. However, this is still a topic without established conclusions. Although many studies describe social media as important tools to improve the learning of health students regarding communication, professionalism and ethics, limitations related to health information found in social media are the lack of quality and reliability. In conclusion, we recognize the numerous potential strengths of social media as educational tools, but many points are still unclear and need to be persistently understood, evaluated, and discussed.